Three phase inverter for induction motor control using fuzzy-pi controller with arduino - Saad, Abdul Salam (2014)
In this project, the main focus is the development of the three phase inverter for induction motor using Fuzzy-PI controller with Arduino. The Fuzzy-PI controller is designed using the Matlab’s Simulink program software. The purpose of the controller is to control the current fed to the induction motor during motor operation. Using this Fuzzy-PI control algorithm, the speed of the running motor can be adjust depend on the DC voltage input which also effect the current flow into the induction motor. There are two situations being test in this project, which is open loop and close loop control scheme. Both situations are covered in both simulation and real hardware testing. The result of the open loop testing and the close loop testing are being compared as the performance indicator. The close loop control scheme show a good ability and responsive in current control for induction motor operation as compared to open loop control.